Contribution to the knowledge of the mayfly genus Ephemera Linnaeus, 1758 (Insecta: Ephemeroptera) with description of four new species from the Western Ghats, India - Muthukatturaja, Marimuthu; Balasubramanian, Chellaiah; Kubendran, Thangavel; Banerjee, Dhriti (Zootaxa, 2026)
The present study provides an integrative taxonomic assessment of the burrowing mayfly family Ephemeridae (Ephemeroptera) from the Western Ghats, India, through a combination of morphological and molecular approaches. Four new species viz., Ephemera kapilaensis sp. nov., Ephemera kodai sp. nov., Ephemera kudremukha sp. nov., and Ephemera subramanyai sp. nov., are described based on both larval and imaginal characters. This work provides the first molecular characterization of Ephemera species from southern India and generates the first DNA barcodes for the subgenus Ephemera in this region. The finding highlights the importance of integrative taxonomy in resolving species boundaries and evolutionary relationships among Oriental Ephemera. Additionally, the study provides distributional data, habitat ecology of the new species, and an identification key to all known species of the Western Ghats.